2011
DOI: 10.1080/09602011.2010.543867
|View full text |Cite
|
Sign up to set email alerts
|

Assessing executive performance during cognitive rehabilitation

Abstract: Executive functioning influences a host of other cognitive processes and people who attend neuropsychological services are more likely to display executive dysfunction than any other cognitive deficit (Stuss & Levine, 2002). Impairment in executive functioning disrupts a person's ability to effectively employ their intact areas of functioning, and undermines effective self-management of other areas of dysfunction, hampering attempts to employ compensatory strategies. Therefore, assessment of a person's executi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 58 publications
(84 reference statements)
3
31
0
1
Order By: Relevance
“…The use of standardised questionnaires have become widespread allow patients and carers to communicate everyday problems, providing opportunities to identify personally relevant goals for rehabilitation, (Hart & Evans, 2006;Lewis, Babbage & Leathem, 2011). The Dysexecutive Questionnaire was developed as an informant (DEX-I) and self-rating scale (DEX), sampling everyday problems commonly associated with executive dysfunction, (Wilson, Alderman, Burgess, Emslie & Evans, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…The use of standardised questionnaires have become widespread allow patients and carers to communicate everyday problems, providing opportunities to identify personally relevant goals for rehabilitation, (Hart & Evans, 2006;Lewis, Babbage & Leathem, 2011). The Dysexecutive Questionnaire was developed as an informant (DEX-I) and self-rating scale (DEX), sampling everyday problems commonly associated with executive dysfunction, (Wilson, Alderman, Burgess, Emslie & Evans, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Since EF is crucial in managing new situations, and a test can only be new once, tests of EF might face particular test-retest reliability issues (Burgess, Alderman, Evans, Emslie & Wilson, 1998). Neuropsychological measures typically capture only certain aspects of EF, and may thus not accurately reflect dysfunction in everyday life (Lewis et al, 2011;Spikman et al, 2010). It has been suggested that performance-based measures and subjective ratings of EF assess different aspects of cognitive and behavioural functioning that independently contribute to clinical problems (Toplak et al, 2012).…”
Section: The Use Of Neuropsychological Tests As Outcome Measures Raismentioning
confidence: 99%
“…Executive dysfunction (ED) is common following acquired brain injury (ABI) (Stuss & Levine, 2002;Novakovic-Agopian et al, 2011), and may disrupt the ability to effectively use intact functions or compensatory strategies, undermine efficient self-management (Lewis, Babbage & Leathem, 2011), hamper the rehabilitation process (Robertson & Murre, 1999), and is also associated with long-term negative psychosocial and vocational outcome (Draper & Ponsford, 2008; Ylvisaker & Feeney, 2000). Thus, techniques for reducing ED might significantly impact functional outcome (Manly & Murphy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Krasny-Pacini et al [14] and Lewis et al [4] described the lack of ecological validity in many executive function measures and the limitations of measures that are more functionally based. Functional measures often lack standardization, norms, and adequate test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, disorganization as a result of executive dysfunction is the most common complaint in individuals with traumatic brain injury (TBI) [2]. Executive deficits may be expected to lead to functional deficits in a broad range of cognitive, emotional, and social skills [3], though more data are needed about how laboratory-based measures of executive dysfunction map onto real-life skills [4].…”
Section: Introductionmentioning
confidence: 99%